Polymerase chain reaction/electrospray ionization–mass spectrometry (PCR/ESI-MS) is not suitable for rapid bacterial identification in peritoneal dialysis effluent. Issue 1 (January 2021) - Szeto, Cheuk Chun; Ng, Jack Kit-Chung; Fung, Winston Wing-Shing; Lai, Ka-Bik; Chow, Kai-Ming; Li, Philip Kam-Tao; Massiah, Arikana; Alcolea-Medina, Adela; Wilks, Mark; Fan, Stanley L
Background: Peritoneal dialysis (PD)-related peritonitis is a serious complication of PD, but routine microbiological culture is slow and could not identify the organism in 15% cases. We examine the accuracy of polymerase chain reaction/electrospray ionization–mass spectrometry (PCR/ESI-MS), a PCR-based method developed for the direct detection of bacteria in blood, for rapid identification of microorganisms from PD effluent. Methods: We recruited 73 consecutive patients with PD-related peritonitis. Dialysis effluent was collected for routine bacterial culture, PCR/ESI-MS, and bacterial DNA quantification before initiation of antibiotic therapy. Results: By digital PCR with universal bacterial primers, bacterial DNA was detectable in all PD effluent specimens. For the entire cohort, taking standard bacterial culture as the gold standard, the PCR/ESI-MS assay correctly identified 34.3% of the causative organisms, failed to identify any organism in 52.1% cases, and identified a different organism in 8.2% cases. For the 14 episodes of peritonitis that were culture negative by conventional bacterial culture, the PCR/ESI-MS assay identified an organism in only four cases. The detection rate of the IRIDICA BAC BSI assay was not affected by the use of biocompatible PD solution or concomitant exit-site infection. Conclusions: The PCR/ESI-MS assay could not identify the causative organism in over 50% of the PD effluent samples in patients with PD-related peritonitis and should be not used for such purpose. The reason for the poor performance needs further investigation.